Detection of Inter-Lineage Natural Recombination in Avian Paramyxovirus Serotype 1 Using Simplified Deep Sequencing Platform - Satharasinghe, Dilan A.; Murulitharan, Kavitha; Tan, Sheau W.; Yeap, Swee K.; Munir, Muhammad; Ideris, Aini; Omar, Abdul R. (Frontiers in Microbiology, 2016)
Newcastle disease virus (NDV) is a prototype member of avian paramyxovirus serotype 1 (APMV-1), which causes severe and contagious disease in the commercial poultry and wild birds. Despite extensive vaccination programs and other control measures, the disease remains endemic around the globe especially in Asia, Africa, and the Middle East. Being a single serotype, genotype II based vaccines remained most acceptable means of immunization. However, the evidence is emerging on failures of vaccines mainly due to evolving nature of the virus and higher genetic gaps between vaccine and field strains of APMV-1. Most of the epidemiological and genetic characterizations of APMVs are based on conventional methods, which are prone to mask the diverse population of viruses in complex samples. In this study, we report the application of a simple, robust, and less resource-demanding methodology for the whole genome sequencing of NDV, using next-generation sequencing on the Illumina MiSeq platform. Using this platform, we sequenced full genomes of five virulent Malaysian NDV strains collected during 2004-2013. All isolates clustered within highly prevalent lineage 5 (specifically in lineage 5a); however, a significantly greater genetic divergence was observed in isolates collected from 2004 to 2011. Interestingly, genetic characterization of one isolate collected in 2013 (IBS025/13) shown natural recombination between lineage 2 and lineage 5. In the event of recombination, the isolate (IBS025/13) carried nucleocapsid protein consist of 55-1801 nucleotides (nts) and near-complete phosphoprotein (1804-3254 nts) genes of lineage 2 whereas surface glycoproteins (fusion, hemagglutinin-neuraminidase) and large polymerase of lineage 5. Additionally, the recombinant virus has a genome size of 15,186 nts which is characteristics for the old genotypes I to IV isolated from 1930 to 1960. Taken together, we report the occurrence of a natural recombination in circulating strains of NDV in commercial poultry using next generation sequencing methodology. These findings will not only highlight the potential of RNA viruses to evolve but also to consider the application of NGS in revealing the genetic diversity of these viruses in clinical materials. Factors that drive these evolutionary events and subsequent impact of these divergences on clinical outcome of the disease warrant future investigations.